Stigma and discrimination: Barrier for ending AIDS by 2030 and achieving the 90-90-90 targets by 2020 - Dewa Nyoman Wirawan (Universitas Udayana, 2019)
In order to be able to mirror the achievements of other countries towards 90-90-90, addressing stigma and discrimination towards key populations and people with HIV+ is crucial. Without these efforts ending the AIDS epidemic by 2030 will be challenging to realize and remain a lofty aspiration.